Prospective, Randomized, Double‐Blind, Parallel‐Group, Comparative Effectiveness Clinical Trial Comparing a Powder Vehicle Compound of Vitamin D With an Oil Vehicle Compound in Adults With Cystic Fibrosis. (22nd February 2016) - Hermes, Wendy A.; Alvarez, Jessica A.; Lee, Moon J.; Chesdachai, Supavit; Lodin, Daud; Horst, Ron; Tangpricha, Vin
Abstract : Background: There is little consensus on the most efficacious vehicle substance for vitamin D supplements. Fat malabsorption may impede the ability of patients with cystic fibrosis (CF) to absorb vitamin D in an oil vehicle. We hypothesized that vitamin D contained in a powder vehicle would be absorbed more efficiently than vitamin D contained in an oil vehicle in patients with CF. Methods: In this double‐blind, randomized controlled trial, hospitalized adults with CF were given a one‐time bolus dose of 100, 000 IU of cholecalciferol (D3 ) in a powder‐based or oil‐based vehicle. Serum D3, 25‐hydroxyvitamin D, and parathyroid hormone concentrations were analyzed at 0, 12, 24, and 48 hours posttreatment. The area under the curve for serum D3 and the 12‐hour time point were also assessed as indicators of D3 absorption. Results: This trial was completed by 15 patients with CF. The median (interquartile range) age, body mass index, and forced expiratory volume in 1 second were 23.7 (19.9–33.2) years, 19.9 (18.6–22.6) kg/m 2, and 63% (37%–80%), respectively. The increase in serum D3 and the area under the curve was greater in the powder group ( P = .002 and P = .036, respectively). Serum D3 was higher at 12 hours in the powder group compared with the oil group ( P = .002), although levels were similar between groups by 48 hours. Conclusions: In adults with CF, cholecalciferol is more efficiently absorbed in a powder compared with an oil vehicle. Physicians should consider prescribing vitamin D in a powder vehicle in patients with CF to improve the absorption of vitamin D from supplements.